Observation of peers in learning to write: Practice and research - Rijlaarsdam, Gert (Journal of Writing Research, 2008)
Elke Van Steendam, Anne Toorenaar,Journal of Writing Research 1(1), 53-83In this paper we discuss the role of observation in learning to write. We argue that the acquisition of skill in such a complex domain as writing relies on observation, the classical imitatio. An important phase in learning to write, at all ages, is learning to write by observing and evaluating relevant processes: writing processes, reading processes or communication processes between writers and readers.First, we present two practical cases: writing lessons in which observation and inquiry are amongst other key elements and where students participate in a community of learners. Then, we review research that may inspire and substantiate proposals for implementing observation as a learning activity in writing education. Two types of studies are discussed: studies in which learners acquire strategies by observing and evaluating writing and reading processes of peers, as a prewriting instructional activity, and studies in which learners are stimulated to 'pre-test' and then revise their first draft, as a post writing instructional activity. The paper closes with some recommendations for further research.